Satisfaction Analysis of Maxim Online Transportation Services in Pandeglang District - Masroni; Sjaiful Akbar; Ero Sukarna; Hanifah; Siti Yuniar (Indonesian Journal of Social Science Research, 2025)
The world has entered the era of industrial revolution 4.0 which has an impact on the development of information and communication technology and the social dynamics therein. One example of technology in the service sector is online transportation. Currently, online transportation can be accessed by all people using smartphones, one of which is Maxim online transportation. This activity aims to find out the level of satisfaction of users of MAXIM online transportation services in Pandeglang Regency. The research approach used was quantitative descriptive analysis. Data collection techniques were used by distributing questionnaires, observation and literature study. The research population is online transportation users in Pandeglang Regency. The sampling technique used was purposive sampling with a total sample of 40 respondents. The data analysis technique was quantitative descriptive analysis. The research results show that Maxim Pandeglang consumers feel that the service provided is very satisfying. This can be seen from the satisfaction score for all service indicators (system mechanisms and procedures; order completion time; costs/tariffs; product specifications, type of service; competence of implementers; behavior of implementers (drivers); handling complaints, suggestions and input) which reaches a maximum score of at least 90 percent. The era of the Industrial Revolution 4.0 has significantly impacted information and communication technology (ICT) and social dynamics. This revolution enhances the growth of service sector technologies such as online transportation. Maxim as one of the key players in the industry of online transportation amplified this trend. The objective of this study to identify the satisfaction of Maxim’s online transportation in Pandeglang using a quantitative descriptive analysis. The data were collected from a purposive sampling of 40 online transportation customers through questionnaires. The findings of this study indicate a high level of user satisfaction which reaches at least 90 percent such as system mechanisms and procedures; order completion time; costs/tariffs; product specifications, type of service; competence of implementers; behavior of implementers (drivers); handling complaints, suggestions and input.